The economic and environmental sustainability dimensions of agriculture: a trade-off analysis of Italian farms - Arru, Brunella; Cisilino, Federica; Sau, Paola; Furesi, Roberto; Pulina, Pietro; Madau, Fabio A. (Frontiers in Sustainable Food Systems, 2024)
Crop and livestock farms are central to achieving the 2030 Agenda goals and a sustainable agri-food system. However, the transition toward a sustainable agri-food system requires optimizing several economic and environmental farm targets that, interacting with one another, would lead to win-win opportunities, at least as desired by the European Union (EU) policies. Indeed, in recent years, the EU has fostered sustainable development in a logic of synergy between farms’ environmental and economic performances. This work fits into the agricultural sustainability assessment with the aim of improving our understanding of the existence of synergy or a trade-off between the economic and environmental dimensions at a crop and livestock field and farm scale. Specifically, using a set of appropriate agricultural economic and environmental indicators, two composite indexes were created and used to perform trade-off analysis on 7.891 farms that participated in 2019 and 2020 in the Italian Farm Accountancy Data Network. The findings showed a trade-off between economic and environmental dimensions in all livestock sub-sectors and the cereals sector, while a synergy in the horticulture sector. Considering the new European sustainability policies on agriculture and global scenarios, the study significantly contributes to policymakers, practitioners, and academic debate on sustainability in agriculture.